2016
DOI: 10.1111/bjh.13928
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of C‐terminal telopeptide of type 1 collagen in multiple myeloma

Abstract: Myeloma bone disease (MBD) is a major cause of morbidity in multiple myeloma (MM). We investigated bone turnover markers (BTM) as relapse predictors and biomarkers for monitoring MBD. We measured C-terminal telopeptide of type I collagen (CTX-1), and Procollagen type 1 N Propeptide (P1NP) in 86 MM patients and 26 controls. CTX-1 was higher in newly diagnosed patients compared to control, remission and relapse (P < 0·05), and decreased following treatment. In the setting of relapse, a CTX-1 rise greater than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…Ting et al presented in a research paper, a significantly elevated level of CTX-1 in patients with lytic lesions, whose MRI showed no bone marrow abnormalities or lytic bone destruction. The study conclusions highlight the important role of CTX-1 in predicting subclinical bone disease before lithic bone destruction occurs (38).…”
Section: Amino-and Carboxy-terminal Cross-linking Telopeptide Of Type I Collagenmentioning
confidence: 76%
See 2 more Smart Citations
“…Ting et al presented in a research paper, a significantly elevated level of CTX-1 in patients with lytic lesions, whose MRI showed no bone marrow abnormalities or lytic bone destruction. The study conclusions highlight the important role of CTX-1 in predicting subclinical bone disease before lithic bone destruction occurs (38).…”
Section: Amino-and Carboxy-terminal Cross-linking Telopeptide Of Type I Collagenmentioning
confidence: 76%
“…The degree of imbalance between bone resorption and bone formation can be expressed by the ratio of β-CTx/PINP (type I procollagen amino terminal propeptide). Studies have shown that CTx and PINP are important parameters values for clinical evaluation of osteoclast and osteoblast activity (38).…”
Section: β-Crosslaps (β-Ctx)mentioning
confidence: 99%
See 1 more Smart Citation
“…MGUS and SMM are associated with osteopenia, altered bone microstructure, and an increased rate of bone resorption and overall fracture risk ( 11 , 12 , 20 ). Biochemical markers of bone resorption such as serum carboxy-terminal telopeptide of type-I collagen (CTX-1) and urine deoxypyridinoline (DPD) correlate with disease burden in patients with MGUS as compared with MM ( 21 , 22 ), and MGUS patients have reduced levels of bone-specific alkaline phosphatase, a cell membrane-associated enzyme produced by osteoblasts, as compared to patients with non-malignant osteoporosis ( 23 ).…”
Section: Pathophysiology Of Myeloma Bone Diseasementioning
confidence: 99%
“…Marķieri ir prognostiski faktori, kas var paredzēt ar skeletu saistītu notikumu attīstības risku un kaulu bojājumu progresiju MM pacientiem. Tos izmanto arī antirezorbtīvās terapijas efekta noteikšanā un pacientu ar augstu slimības progresijas risku identifikācijai(Lipton et al, 2007(Lipton et al, , 2010Chu et al, 2016;Ting et al, 2013Ting et al, , 2016. Šie tipi savukārt ir iedalīti 3 mielomas šūnu prognostiskās grupās: zemas malignitātes (Maršalko un sīko/mazo šūnu), vidējas malignitātes (šķelto šūnu, polimorfo un asinhrono) un augstas malignitātes pakāpes (plazmoblastisko šūnu tips)(Bartl et al, 1987).Bisfosfonāti nesamazina jau esošus kaulu bojājumus, bet tie novērš un aizkavē jaunu bojājumu veidošanos.…”
unclassified